Zola's Une page d'amour: the novelist as Japanese artist - Yee, J (Oxford University Press, 2024)
In the 1860s and 1870s Japanese art inspired great enthusiasm in France, both in fashionable Parisian circles and among artists. A dual response to this art underlies Émile Zola’s novel Une page d’amour (1878). The novel shows us japonaiserie — the fashionable collection and imitation of Japanese objects for their exotic appeal — in the Japanese pavilion decorated by a society hostess, and in fancy dress costume worn by the heroine Hélène’s daughter. This japonaiserie is portrayed through ekphrasis, the verbal representation of visual representation. Japanese art also influences description in Une page d’amour, and most of all the five great cityscapes that show Paris seen from Hélène’s apartment at different times of day. Here however Zola is demonstrating that true art responds to the new forms of Japanese art not through mere exoticism, but through a deeper transformation of our way of seeing the world: japonisme. These descriptions use pictorialism, in which verbal art recreates the effects of visual art. Zola’s contrast of japonaiserie and japonisme via ekphrasis and pictorialism respectively is a means to assert the superiority of his own verbal art.